2020
DOI: 10.1371/journal.pone.0231262
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nasal and oral breathing on airway collapsibility in patients with obstructive sleep apnea: Computational fluid dynamics analyses

Abstract: The purpose of this study was to investigate the effect of breathing route on the collapsibility of the pharyngeal airway in patients with obstructive sleep apnea by using computational fluid dynamics technology. MethodsThis study examined Japanese men with obstructive sleep apnea. Computed tomography scans of the nose and pharynx were taken during nasal breathing with closed mouth, nasal breathing with open mouth, and oral breathing while they were awake. Three-dimensional reconstructed stereolithography mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…Our previous studies [ 19 , 20 , 23 ] demonstrated that CFD simulations could largely reproduce patients’ actual respiratory flow dynamics. This study suggests that CFD can be used to analyze respiration air flows in areas that cannot be measured by rhinomanometric methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies [ 19 , 20 , 23 ] demonstrated that CFD simulations could largely reproduce patients’ actual respiratory flow dynamics. This study suggests that CFD can be used to analyze respiration air flows in areas that cannot be measured by rhinomanometric methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Variables included tissue distensibility 10 , speed of injection 11 , patient characteristics 12 , psychological aspects 4 and temperature 13 . Simple and non-medical measures to reduce stress level during dental procedures are preferably adopted [6][7][8] . Nasal breathing is a natural process than oral breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Generally oral breather patients are irritable, stressed out and fatigued whereas nasal breathers have active parasympathetic system than oral breathesr 5 . Also, there is less amount of endogenous epinephrine released in nasal breathers which may contribute to lower anxiety and pain perception 5,6 . Studies have revealed that oral breather has more pain perception than nasal breather during LA in dentistry [5][6][7][8][9] In light of the above, this study was aimed at observing the difference in pain perception during IANB in oral and nasal breather.…”
Section: Introductionmentioning
confidence: 99%
“…Fitzpatrick et al examined healthy subjects to compare nasal and oral breathing routes. The study found that when breathing was through the mouth, upper airway resistance during sleep was 2.5 times greater than when breathing was through the nose [ 72 ]. Hsu et al reported that mouth breathing was strongly associated with greater oxygen desaturation and more significant upper airway collapse.…”
Section: Applying the Three Dimensions Of Breathing Re-education Tmentioning
confidence: 99%